Chronic Pruritus in the Absence of Skin Disease: Pathophysiology, Diagnosis and Treatment - Pereira, Manuel P.; Kremer, Andreas; Mettang, Thomas; Staender, Sonja (American Journal of Clinical Dermatology, 2016)
Chronic pruritus arises not only from dermatoses, but also, in up to half of cases, from extracutaneous origins. A multitude of systemic, neurological, psychiatric, and somatoform conditions are associated with pruritus in the absence of skin disease. Moreover, pruritus is a frequently observed side effect of many drugs. It is therefore difficult for physicians to make a correct diagnosis. Chronic pruritus patients frequently present to the dermatologist with skin lesions secondary to a long-lasting scratching behavior, such as lichenification and prurigo nodularis. A structured clinical history and physical examination are essential in order to evaluate the pruritus, along with systematic, medical history-adapted laboratory and radiological tests carried out according to the differential diagnosis. For therapeutic reasons, a symptomatic therapy should be promptly initiated parallel to the diagnostic procedures. Once the underlying factor(s) leading to the pruritus are identified, a targeted therapy should be implemented. Importantly, the treatment of accompanying disorders such as sleep disturbances or mental symptoms should be taken into consideration. Even after successful treatment of the underlying cause, pruritus may persist, likely due to chronicity processes including peripheral and central sensitization or impaired inhibition at spinal level. A vast arsenal of topical and systemic agents targeting these pathophysiological mechanisms has been used to deter further chronicity. The therapeutic options currently available are, however, still insufficient for many patients. Thus, future studies aiming to unveil the complex mechanisms underlying chronic pruritus and develop new therapeutic agents are urgently needed.
EVALuna2:2197